Stress, Psychopathological Symptoms and Risk of Clicking in College Students: A Case-Control Study (2015)
Introduction: scientific evidence suggests that stress and psychological symptoms play an important role on diseases. The aim of this study was to investigate clicking in individuals with stress and different psychopathological symptoms. Methods: we compared 30 college students who experienced clicking with 60 healthy control volunteers. The participants received the pss-10 and scl-90-r Spanish versions. Odds ratio (or) and 95% ci were calculated to determine the risk of these variables for the presence of clicking using logistic regression. Results: stress was weakly associated with the occurrence of clicking (or = 1.35, 95% ci: 0.46-3.95, p = 0.57). Being an individual with stress and depression (or = 2.92, 95% ci: 0.61-14.0, p = 0.16) and anxiety (or = 2.80, 95% ci: 0.69-11.31, p = 0.13) may increase the risk of clicking. In addition, depression (or = 7.00, 95% ci: 0.66–74.28, p = 0.07) and anxiety (or = 4.90, 95% ci: 0.78 – 30.80, p = 0.07) adjusted by pain symptoms seem to be important variables for some subjects. The risk of clicking in students with anxiety-depression comorbidity and stress was higher (or = 2.11, 95% ci: 0.40-11.15, p = 0.37). Moreover, there was a different risk when this comorbidity, stress and pain symptom were present (or = 4.30, 95% ci: 0.35-51.90, p = 0.21). Conclusion: depression, anxiety, stress and pain may be predictors for development of TMD such as clicking. In this sense, the measurement of those conditions in these patients should be a priority.